Characterization of the hydroxyproline-rich protein core of an arabinogalactan-protein secreted from suspension-cultured Lolium multiflorum (Italian ryegrass) endosperm cells. - Gleeson, P A (1989)
An arabinogalactan-protein (AGP) purified from the filtrate of liquid-suspension-cultured Italian-ryegrass (Lolium multiflorum) endosperm cells by affinity chromatography on myeloma protein J539-Sepharose was deglycosylated with trifluoromethanesulphonic acid to remove polysaccharide chains that are covalently associated with hydroxyproline residues in the peptide component of the proteoglycan. The protein core, which accounts for less than 10% (w/w) of the intact proteoglycan, was purified by h.p.l.c. It has an apparent Mr of 35,000, but reacts very poorly with both Coomassie Brilliant Blue R and silver stains. Amino-acid-sequence analysis of the N-terminus of the h.p.l.c.-purified protein core and of tryptic peptides generated from the unpurified protein reveals a high content of hydroxyproline and alanine. These are sometimes arranged in short (Ala-Hyp) repeat sequences of up to six residues. Polyclonal antibodies raised against the protein core do not cross-react with native AGP, the synthetic peptide (Ala-Hyp)4, poly-L-hydroxyproline or poly-L-proline. The results suggest that the polysaccharide chains in the native AGP render the protein core of the proteoglycan inaccessible to the antibodies and that the immunodominant epitopes include domains of the protein other than those rich in Ala-Hyp repeating units.